Multistep microsatellite mutation in a case of non-exclusion parentage. (May 2015) - Liu, Yu Xuan; Zhang, Wen Qiong; Jia, Yun Shu; Zhang, Lei; Zhou, Feng Lei; Mei, Kun; Huang, Dai Xin; Yi, Shao Hua
Highlights: A non-exclusion paternity case revealed a four or six step mutation at D5S818 locus. The alleles in the mother, the child and the father were 13, 11/13 and 7/13. The combined paternity index of 39 autosomal STRs is up to 2.461 × 10 9 . Genotyping of 16 Y-STR loci in the child matched completely with the father. Abstract: A non-exclusion paternity with multistep mutation in the locus D5S818 was reported. Examination of 39 autosomal short tandem repeats (STR) loci revealed a mismatch of the maternally or paternally transmitted allele in the locus D5S818 in the questioned child. The composition of the alleles of this locus in the mother, the questioned child and the alleged father are 11/13, 7/13 and 13, respectively. The sequence analysis of the regions flanking the locus D5S818 of the mother, the questioned child and the alleged father excluded the possibility of null allele as a cause of the allelic mismatch in the child. The combined paternity index of 39 autosomal STRs is up to 2.461 × 10 9 . Genotyping of sixteen Y-STR loci in the questioned child matched completely with the alleged father. The results prove that the alleged father is the biological father of the questioned child with four-step or six-step microsatellite mutation in the locus D5S818.